Industrial and organisational psychology in Malaysia: a review of research areas and research variables - Mohd. Taib, Maisarah; Alias, Alizi (Pearson, 2012)
The chapter has identified the frequency and rank of research areas and research variables in Malaysia. The effort is inspired by Erez's (1994) study on the frequency of I/O psychology research variables in different countries. Interpretation based on Hofstede's (1980)framework of cultural dimensions shows that cultural dimensions have an influenced on the research variables selected in I/O psychology research in Malaysia.Furthermore, an illustration of I/O psychology research areas and research variables in Malaysia shows that the field has developed more as an academic field but has very little implications in practice.